Local closed world reasoning with description logics under the well-founded semantics - Knorr, Matthias (2019)
We thank the reviewers of a previously submitted version of this paper for their very helpful comments and suggestions for improvement. We thank Frederick Maier for a thorough proofreading. Matthias Knorr acknowledges support by Fundação para a Ciência e a Tecnologia under the grant SFRH/BD/28745/2006. Pascal Hitzler acknowledges support by the National Science Foundation under award 1017225 “III: Small: TROn – Tractable Reasoning with Ontologies”.